Uniting Science and Faith: A Re-STEAM Interdisciplinary Approach in Islamic Education Learning - Adiyono, Adiyono; Fitri, Agus Zaenul; Al Matari, Ali Said (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This study explores the effective Re-STEAM (Religion, Science, Technology, Engineering, Arts, and Mathematics) interdisciplinary approach in teaching Islamic Religious Education (PAI) at SDIT Al-Khawarizmi and SDN 031 Tanah Grogot, Indonesia. The research addresses the need to revitalize PAI learning by integrating it with other disciplines, particularly science and technology. Using qualitative methods with a phenomenological approach and Multi-Site Design, the study investigates the impact of Re-STEAM on student learning outcomes. Results indicate that this approach significantly enhances students' learning motivation, critical thinking skills, and understanding of PAI materials. Integrating science and faith through Re-STEAM helps students apply Islamic values daily and prepares them for 21st-century challenges. Moreover, it demonstrates that modern science complements religious teachings, fostering a balanced development of intellectual, emotional, and spiritual intelligence. The findings suggest that the Re-STEAM approach effectively combines academic competence with strengthened faith and character, aligning with the core principles of Islamic education.